IBM DS8910F Model 993 Rack-Mounted Storage System Release 9.1 - Brunson, Sherry; Dufrasne, Bert; Kimmel, Peter (IBM Redbooks, 2020)
This IBM Redpaper publication presents and positions the DS8910F Model 993 storage system. This modular system can be integrated into a 16U contiguous space of an IBM z15™ model T02 or IBM z14® Model ZR1 with Feature Code 0937 and IBM LinuxONE III model LT2 or LinuxONE Rockhopper II model LR1 with Feature Code 0938. The DS8910F Model 993 allows you to take advantage of the performance boost of all-flash systems and advanced features while limiting data center footprint and power infrastructure requirements.